Gender and Development : An Evaluation of World Bank Support, 2002–08 - World Bank (Washington, DC, 2012)
The World Bank's current gender policy resulted directly from the 2001 gender strategy endorsed by the board. This evaluation which covers the period fiscal 2002-08, finds that the Bank made progress in gender integration compared with an earlier Independent Evaluation Group (IEG) evaluation on gender covering the period fiscal 1990-99. Gender integration into Bank support increased both in quantity and in scope, and more than half of relevant projects integrated gender concerns. With regard to outcomes, detailed reviews were undertaken in 12 focus countries, and the evaluation finds that Bank support likely contributed to increased gender equality in three domains - investment in human capital, access to economic assets and opportunities, and voice in development - substantially in 4 of the 12 countries, modestly in another 6, and weakly in 2. At the project level, 42 percent of relevant projects in the 12 focus countries generated substantial outcomes that contributed to progress in one or more of these domains. The objectives of the Bank's gender policy are directly relevant to the Bank's mandate of poverty reduction and economic development. The evaluation found another factor that also tended to diminish the relevance of the Bank's gender policy, namely the narrowing of the entry point for gender integration at project appraisal to specific priority sectors. The evaluation recommends several actions to regain and sustain the momentum of gender integration that was evident in the first half of the evaluation period. These include redoubling efforts to institutionalize the accountability framework and develop the monitoring system envisioned in the 2001 gender strategy, establishing a results framework, and restoring a broader requirement for gender integration at the project level.